Teaching Teaching and researching. High school physics and chemistry professors at JAE research centersand researching - López Martínez, J. Damián; Delgado Martínez, María Ángeles (CIAN-Revista de Historia de las Universidades, 2023)
In this paper we analyse, firstly, the participation of high school physics and chemistry teachers during the first third of the 20th century in the activities promoted by the Junta para Ampliación de Estudios e Investigaciones Científicas. Secondly, we study how the creation of the Instituto-Escuela of Madrid in 1918, a pedagogical essay dependent on the Junta, provided a new framework to address the renewal of physics and chemistry teaching in secondary education and, at the same time, made possible an intense relationship between university professors who worked as research teachers and secondary school teachers. Finally, we show that with the arrival of the Second Republic, the group of secondary school physics and chemistry professors continued along the path initiated years earlier, spreading and expanding the renewal of Spanish secondary education, and remained committed to the research work carried out at the Instituto Nacional de Física y Química.
Keywords: Junta para Ampliación de Estudios e Investigaciones Científicas; high school physics and chemistry professors; Instituto-Escuela of Madrid; teaching and scientific research